A política de assistência social desenvolvida nos CRAS de Sertãozinho para a prevenção da violência doméstica contra crianças e adolescentes - Bueno, Fabiana de Barros [UNESP] (2015)
Since the time of vessels, children and adolescents suffer from various types of violence. The story of children and adolescents in Brazil, reveals that they were and are still subject to several violent situations and often, this violence occurs within the home. Domestic violence against children and adolescents is a complex phenomenon, difficult to be worked and is characterized as a violation of the rights of children and adolescents, therefore, a policy of social assistance should be developed in CRAS, continuously and effectively to identify the so-called population at risk and a set of actions carried out in conjunction to offer protection and support to families and strategies for their prevention and coping, ensuring thereby protecting and defending the rights of the child and adolescent . Thus, the present study allowed investigate the professional practice of the municipality of CRAS Sertaozinho forward work to identify early cases of domestic violence against children and adolescents. Through semi-structured interviews were chosen two professionals in each CRAS, one coordinator and one Professional Services responsible for Coexistence and Strengthening Linkages. This contact enabled a real grasp of the conditions of work ahead this work to prevent domestic violence against children and adolescents, as well as their difficulties, which can be grasped through this work.